Spindle Epithelial Tumor with Thymus-Like Differentiation (SETTLE): A Case Report. (3rd September 2019) - Matheson, Cyrus L; Blair, Geoffrey K; Bush, Jonathan
Abstract: Background: Spindle epithelial tumor with thymus-like differentiation (SETTLE) is a tumor with an indolent disease course and late metastatic potential. It occurs primarily in children and adolescents, although it can present later in life. It was first described by Chan and Rosai [Tumors of the neck showing thymic or related branchial pouch differentiation: a unifying concept. Hum Pathol. 1991;22(4):349–67. doi:10.1016/0046-8177(91)90083-2], and there have been approximately 46 cases published in the English literature.Case report: We present an 8-year-old female with a SETTLE, undergoing an initial fine-needle aspiration and later a diagnostic biopsy. There is no evidence of disease recurrence at 3.5 years of follow-up.Conclusion: Though fine-needle aspirate biopsy is useful in directing the diagnostic workup of SETTLE by indicating concerning pathology, the broad differential diagnosis associated with it requires histology in conjunction with a limited immunohistochemical panel and unremarkable cytogenetics workup. Surgical resection is the main stay of treatment, and long-term follow-up is important in these patients.